Gender and popular culture - Milestone, Katie; Meyer, Anneke, 1976- (2020)
"An exciting new edition of an important text, updated for the #MeToo era"--
Includes bibliographical references and index.
Keywords: Sex role; Gender identity; Femininity in popular culture; Masculinity in popular culture; Sex role in mass media